The European Nucleotide Archive in 2021. Issue Volume 50:Issue D1(2022) (26th November 2021) - Cummins, Carla; Ahamed, Alisha; Aslam, Raheela; Burgin, Josephine; Devraj, Rajkumar; Edbali, Ossama; Gupta, Dipayan; Harrison, Peter W; Haseeb, Muhammad; Holt, Sam; Ibrahim, Talal; Ivanov, Eugene; et al.
Abstract: The European Nucleotide Archive (ENA, https://www.ebi.ac.uk/ena ), maintained at the European Molecular Biology Laboratory's European Bioinformatics Institute (EMBL-EBI) provides freely accessible services, both for deposition of, and access to, open nucleotide sequencing data. Open scientific data are of paramount importance to the scientific community and contribute daily to the acceleration of scientific advance. Here, we outline the major updates to ENA's services and infrastructure that have been delivered over the past year.